Different Methods of Physical Training Applied to Women Breast Cancer Survivors: A Systematic Review - Schutz, Silvia; Aidar, Felipe J.; Souza, Rafael Luiz Mesquita; dos Santos, Jymmys Lopes; Voltarelli, Fabrício Azevedo; Vieira Junior, Roberto Carlos; Soares, Nara Michelle Moura; Marçal, Anderson Carlos (Frontiers in Physiology, 2021)
Objective: The objective of this systematic review was to identify the effects of different training methods in women who have survived breast cancer (WSBC). Data Sources: Studies were identified by searching SportDiscus, Web of Science, PubMed, Scopus, Scielo, and Bireme. Study Selection: The inclusion criteria were articles that addressed only breast cancer in women, were randomized clinical trials, and interventions involving physical training with Consort ≥80. Data Extraction: The PICO and CONSORT strategies were used for the selection of articles and quality assessment of randomized clinical trials, respectively. Two independent reviewers searched for articles among the databases. Disagreements were discussed, and in the case of an impasse, a third reviewer was consulted. Data Synthesis: Evidence that demonstrated the beneficial effects of physical exercise programs carried out by WSBC. Moderate or high-intensity exercise sessions have been shown to benefit women survivors of breast cancer. Among the modalities, the resistance exercise showed effects from 55% of one-repetition maximum (1 RM), exclusively or associated with other training regimes, such as aerobic (from 48% of heart rate), high-intensity interval training (HIIT), or impact. The main benefits include increased muscle strength, promoted by the practice of resistance exercise in combination with other types of exercises or alone; decreased fatigue; improved quality of life; improved psychosocial effects, and increased leisure time. Conclusions: Physical training performed at a moderate or high intensity (aerobic or anaerobic) can reduce fatigue, improve quality of life, improve sleep quality, and increase bone mineral density in women survivors of breast cancer.